Implementation of a MIS tool based on open XML - Baniani, Behdad (2009)
The purpose of this project is to develop a MIS (Management Information System) based on Open XML standard which could be supported in Microsoft Excel Application therefore; this system can use all the Microsoft Excel features. SolonExcel provides possibility to create a template which contains layout and data model of the report. Reports are being generated by the mentioned templates, in this case customized report based on desired data and query is provided in Microsoft Excel file format which can be more customized with Microsoft Excel Application. The system is developed as a three tiers model and running over intranet. This software is not a decision maker it is just a tool to help decision makers to have a better decision.The methodology for the project is V-Model. Analyzing and development of design and requirements are done by Unified Modeling Language 2.0 also known as UML. The system was built on .Net framework platform. This software is a product of Pentasoft Sdn. Bhd.